Differential effects of glyoxalase 1 overexpression on diabetic atherosclerosis and renal dysfunction in streptozotocin‐treated, apolipoprotein E‐deficient mice. Issue 6 (11th June 2014) - Geoffrion, Michèle; Du, Xueliang; Irshad, Zehra; Vanderhyden, Barbara C.; Courville, Kerri; Sui, Guangzhi; D'Agati, Vivette D.; Ott‐Braschi, Sylvie; Rabbani, Naila; Thornalley, Paul J.; Brownlee, Michael; Milne, Ross W.
Abstract The reactive dicarbonyls, glyoxal and methylglyoxal (MG), increase in diabetes and may participate in the development of diabetic complications. Glyoxal and MG are detoxified by the sequential activities of glyoxalase 1 (GLO1) and glyoxalase 2. To determine the contribution of these dicarbonyls to the etiology of complications, we have genetically manipulated GLO1 levels in apolipoprotein E‐null (Apoe−/−) mice. Male Apoe−/− mice, hemizygous for a human GLO1 transgene (GLO1TGApoe−/− mice) or male nontransgenic Apoe−/− litter mates were injected with streptozotocin or vehicle and 6 or 20 weeks later, aortic atherosclerosis was quantified. The GLO1 transgene lessened streptozotocin (STZ)‐induced increases in immunoreactive hydroimidazolone (MG‐H1). Compared to nondiabetic mice, STZ‐treated GLO1TGApoe−/− and Apoe−/− mice had increased serum cholesterol and triglycerides and increased atherosclerosis at both times after diabetes induction. While the increased GLO1 activity in the GLO1TGApoe−/− mice failed to protect against diabetic atherosclerosis, it lessened glomerular mesangial expansion, prevented albuminuria and lowered renal levels of dicarbonyls and protein glycation adducts. Aortic atherosclerosis was also quantified in 22‐week‐old, male normoglycemic Glo1 knockdown mice on an Apoe−/− background (Glo1KDApoe−/− mice), an age at which Glo1KD mice exhibit albuminuria and renal pathology similar to that of diabetic mice. In spite of 75% decrease in GLO1 activity and increased aortic MG‐H1, the Glo1KDApoe−/− mice did not show increased atherosclerosis compared to age‐matched Apoe−/− mice. Thus, manipulation of GLO1 activity does not affect the development of early aortic atherosclerosis in Apoe−/− mice but can dictate the onset of kidney disease independently of blood glucose levels.